Histopathology and Long-Term Outcome of Kidneys Transplanted From Donors With Severe Acute Kidney Injury. (March 2019) - Cima, Luca; Nacchia, Francesco; Ghimenton, Claudio; Valotto, Giovanni; Boschiero, Luigino; Gobbo, Stefano; Zaza, Gianluigi; Neil, Desley; Mescoli, Claudia; Vanzo, Francesca; D'Errico, Antonietta; Ghimenton, Caterina; et al.
Background: Acute kidney injury is a treatable entity although difficult to recognize without diagnostic biopsy. We investigated the potential association between clinically defined deceased donors and acute kidney injury with preimplantation histological findings and recipient outcomes. Methods: Kidney biopsies from donors were classified using the Acute Kidney Injury Network criteria and assessed for percentage glomerulosclerosis, tubular atrophy, interstitial fibrosis, and vascular narrowing with the Remuzzi score and for acute tubular necrosis. Differences in incidence rates of delayed graft function (DGF) and cumulative rejection episodes were compared between recipients transplanted with normal and 3 levels of acute kidney injury using the analysis of variance with Bonferroni correction ( P = .0012). Results: Sixteen out of 335 donors showed a severe acute kidney injury level 3 with a median serum creatinine of 458 µmol/L. Fourteen (88%) had 0-3 Remuzzi score and were used for single kidney transplantation and 2 (12%) were used for dual kidney transplantation (score: 4-6). Recipients who received a kidney from a donor with level 3 acute kidney injury had a higher percentage of DGF (47%) without statistical significance ( P = .008). The rate of cumulative rejection (45%) at 2 years was not significantly increased ( P = .09). Conclusions: Recipients receiving level 3 acute kidney injury kidneys, selected with Remuzzi histopathological score and acute tubular necrosis assessment, had a greater incidence of DGF but a similar long-term cumulative rejection compared to no injury and level 1 and level 2 acute kidney injury donors. The application of the histopathological examination allowed expansion of the kidney donor pool.